Memoria histórica del grupo rockero al Sur del Cielo. - Choez Cueva, Diana Gabriela (2016)
This article discusses the emergence and evolution of the South Corporation Rocker Cultural Al of Heaven, which is an important element in the Ecuadorian cultural diversity. The objective pursued is the development of the historical memory of that cultural organization as well as the obstacles and challenges it has faced in its development. To display the theme we started with a series of questions that guided the author in collecting data and more relevant to the reconstruction of the history of the Corporation information. Selected for the historical study methodology is qualitative, as this allows entering and interpreting the perceptions about the development of culture in Ecuador rocker, and the impact on the lives of exponents and followers of the genre. The type of study is descriptive, which is consistent with the investigative tools applied: the interview and document analysis. The historical memory presented on these pages collects and presents the major milestones that have marked the development of rocker movement in the country, which is now fundamental part of the diverse framework, culturally speaking, that is Ecuador. The most important conclusion is arrived at work it is that the development of the Ecuadorian rocker movement until its institutionalization in the Corporation Rocker Cultural South of Heaven, has been plagued by obstacles that have circumvented thanks to the perseverance and love Ecuadorian rockers to this culture.